Introduction to the Special Section: Suicide Risk Assessment and Intervention in School Counselor Training - Lucy L Purgason; Christian D. Chan; Bradley McKibben (Teaching and Supervision in Counseling, 2022)
This special section on school counselor preparation in assessing for crisis and suicide risk considers the impact of the perception of school counselor training and expertise related to suicide assessment and intervention. The collection of six articles focuses on considerations and best practices in assessing and intervening with PK-12 students experiencing suicidality, the unique considerations within a school setting, and corresponding implications for school counselor training.
Keywords: suicide; crisis; assessment; school counseling; counselor training